Health, empowerment and triangulation - Lefèvre, Fernando; Lefèvre, Ana Maria Cavalcanti (Saúde e Sociedade, 2004)
In this article health is focused by three points of view: of the individual, of the productive system and of the technician. For the individual, health is viewed as a sensation (of non-disease, of no-pain, etc); for the productive system, health is viewed as a value to be offered in the private and public market; and for the technician, as a power to provide health. From these three points of view, many interactions can be obtained. In the web of nteractions, empowerment is important, as the individual can be seen as the weakest actor.